The impact of independent learning on students’ accounting learning outcomes at vocational high school - Ery Novita Sari; Zamroni Zamroni (Jurnal Pendidikan Vokasi, 2019)
The independence of student learning in recent years was discussed in several articles. Through the development of an independent attitude in learning, students can diagnose learning difficulties and find the right solution to solve them. This study was aimed at finding out how the influence of learning independence on students' accounting learning outcomes. The type of research used is ex-post facto quantitative research. The population of the research is all students of class XI of Public Middle School in the city of Yogyakarta, with a total of 156 students. The instruments used were questionnaires and multiple-choice questions (MCQs). Validity and reliability of the questionnaire were measured using Confirmatory Factor Analysis (CFA) through the Lisrel 8.80 application, while the validity and reliability of MCQs were measured using Rasch approach through the Quest application. Several questionnaires in the form of questionnaires and documentation were used on the testing instrument. The number of instruments for learning independence was 19 statements. The closed statement form used a Likert scale consisting of five alternative answers. The number of MCQs is 18 questions. There were 18 valid statements found after going through the calculation of validation, reliability, difficulty level of the question, and distinguishing power. Simple regression was used for the data analysis technique. The results of the study show that the learning independence variable has a significant and positive influence. It can be seen from the learning independence variable, which has a value of 2.187 and a significance value smaller than 0.05 (0.030 <0.05).